Language and Islamic Review of the Phenomenon of Language Insensitivity in Social Education Environment - Risris Hari Nugraha; Muhamad Parhan; Lestari Kusuma Dewi; Mia Amanda; Riko Arrasyid (Jurnal Pendidikan Ilmu Sosial, 2022)
This study aims to determine the phenomenom of language impoliteness in social educational environments. Language politeness is used by the community by paying attention to the social relations between speakers, listeners, status, and intimacy. Meanwhile, impoliteness of language is an attitude that is contrary to politeness values and has a negative tendency. The method used in study is a mixed method, The design used is a descriptive analysis with the theory of Culpeper's disharmony strategy and Qur'anic communication theory. The result of this study shows that of the ten impolite words that are often used by students in social educational environment, there are two Sundanese words that have highest percentage, namely “maneh” which often heard by 83% and the word “aing” which is often uttered by 38%. Culpeper impoliteness strategy forms that are often used are positive and negative impoliteness, while the concept of Qur’anic communication that is often violated is the principle of qoulan ma’rufa, qoulan maisura, qoulan layyina, and qoulan karima.